Identifying content-based and relational techniques to change behaviour in motivational interviewing. Issue 1 (2nd January 2017) - Hardcastle, Sarah J.; Fortier, Michelle; Blake, Nicola; Hagger, Martin S.
ABSTRACT: Motivational interviewing (MI) is a complex intervention comprising multiple techniques aimed at changing health-related motivation and behaviour. However, MI techniques have not been systematically isolated and classified. This study aimed to identify the techniques unique to MI, classify them as content-related or relational, and evaluate the extent to which they overlap with techniques from the behaviour change technique taxonomy version 1 [BCTTv1; Michie, S., Richardson, M., Johnston, M., Abraham, C., Francis, J., Hardeman, W., … Wood, C. E. (2013). The behavior change technique taxonomy (v1) of 93 hierarchically clustered techniques: Building an international consensus for the reporting of behavior change interventions. Annals of Behavioral Medicine, 46, 81–95]. Behaviour change experts ( n = 3) content-analysed MI techniques based on Miller and Rollnick's [(2013). Motivational interviewing: Preparing people for change (3rd ed.). New York: Guildford Press] conceptualisation. Each technique was then coded for independence and uniqueness by independent experts ( n = 10). The experts also compared each MI technique to those from the BCTTv1. Experts identified 38 distinct MI techniques with high agreement on clarity, uniqueness, preciseness, and distinctiveness ratings. Of the identified techniques, 16 were classified as relational techniques. The remaining 22 techniques were classified as content based. Sixteen of the MI techniques were identified as having substantial overlap with techniques from the BCTTv1. The isolation and classification of MI techniques will provide researchers with the necessary tools to clearly specify MI interventions and test the main and interactive effects of the techniques on health behaviour. The distinction between relational and content-based techniques within MI is also an important advance, recognising that changes in motivation and behaviour in MI is a function of both intervention content and the interpersonal style in which the content is delivered.